Genome-wide analysis of the TCP transcription factor family in mung bean and its dynamic regulatory network under salt stress - Wang, Zhi-Wei; Li, Guan; Li, Ru-Zhi; Tian, Ru-Mei; Liu, Min; Chen, Xue; Hou, Song; Zhao, Jiu-Yan; Yang, Yong-Yi; Xie, Kun; Qin, Na; Wang, Longxin; et al. (Frontiers in Plant Science, 2025)
The TCP gene family encodes plant-specific transcription factors that regulate plant growth, development, and stress responses. Although this gene family has been widely studied in various species, its function in mung bean (Vigna radiata) remains unclear. In this study, we identified 26 VrTCP genes, which were classified into two groups: Class I (PCF subfamily) and Class II (CYC/TB1 and CIN subfamilies). These family members likely function in the nucleus. VrTCP genes are unevenly distributed across chromosomes and are associated with gene duplication events. Their cis-regulatory elements are involved in plant growth, hormone signaling, and stress responses. Co-expression network analysis further supports these findings, identifying 1,304 genes co-expressed with VrTCPs, among which VrTCP19, VrTCP10, VrTCP16, and VrTCP20 act as hub genes regulating hormone signaling and the MAPK pathway. Overall, VrTCP genes play a key role in salt stress responses, providing molecular insights that may facilitate the development of salt-tolerant mung bean varieties through molecular breeding. These findings also offer a foundation for future functional studies aimed at improving crop resilience under abiotic stress conditions.